Effects of Crude Extracts of Areca catechu L. on Locomotory Behaviour in Drosophila melanogaster - US, Upendra Sharma; Iyer, R Shanti (Asian Journal of Biological and Life Sciences)
Background: Areca nut (Areca catechu L.) is a plant of immense economic value in South Asian countries, and has a traditional and aesthetic value in many parts of India. Areca nut has a variety of secondary metabolites such as alkaloids, tannins, flavonoids, and triterpenes. Several conflicting reports have argued about the safety of Areca nut consumption by people across the globe. Materials and Methods: Methanolic extract of the areca nut was fed to Drosophila melanogaster and its effects were investigated by studying their locomotory behaviour. Results: The RING assay and larval crawling assay have been used to study the flies’ locomotory behaviour, and the results were substantially influenced by the various doses of areca nut extract, with the flies appearing lethargic in their movement at higher concentrations. Discussion: Flies reared on a medium containing various concentrations of Areca nut methanolic extracts exhibited variations in their locomotory behaviour. This finding is significant because research conducted by many researchers on Drosophila melanogaster using other substances such as ethanol and caffeine yielded comparable results. Further studies are warranted in order to extrapolate the findings to analyze and understand similar anomalies in higher organisms like humans.
Keywords: Areca catechu L; Arecoline; Drosophila melanogaster; RING Assay